Regional development and internal migration aspects of structural transformation: A case study of Senegal - Mukashov, Askar; Thurlow, James (Kiel Institute for the World Economy, 2023)
This study investigates regional development and internal migration dynamics within the context of modern structural transformation in Sub-Saharan Africa. We develop a regionalized Computable General Equilibrium model that incorporates regionalized production, endogenous interregional migration, and distinct migrant households. Using this model, we simulate the structural transformation of Senegal as a case study. Our findings demonstrate that agricultural stagnation, exacerbated by global climate change, underlies the economic underperformance of rural regions and amplifies regional income disparities. Furthermore, our analysis shows that outmigration from stagnating rural provinces to a more developed capital region positively influences overall economic growth and mitigates regional income inequality. Nevertheless, these effects are limited, and a proactive approach to addressing income inequality across the nation's regions would require supporting agriculture, as it represents a more equitable policy than promoting nonagricultural sectors in both rural and capital regions.